Analytical food microbiology a laboratory manual - Yousef, Ahmed E (Wiley, 2022)
The fully revised second edition presents improved conventional techniques, advanced analytical methodologies, updated content reflecting emerging food safety concerns, and new laboratory experiments incorporating commercially available microbiological media. Throughout the book, clear and concise chapters explain culture- and molecular-based approaches for assessing microbial quality and safety of diverse foods.